Penyuluhan Penginapan di Desa Girijati Gunungkidul - Kurnianingtyas, Chandra Dewi; Angelita Hemar; Mika Evan De Subakti; Giovani Battista Bayu Indra Yanto; Gabrielle Treisyela Dini; Keisha Mei Lagunsad; Bruno Galang Kusuma; Andreas B. Prakoso; Matthew Lareen Kristiawan; Prajna Paramitta; Intan Putri Mellyana (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Community service activities to Girijati Village, Purwosari, Gunungkidul are carried out to make contributions that are expected to be useful. Researchers found the potential for accommodation business, namely the lodging business. There are 32 hotels or inns in Girijati Village. This potential can increase the number of tourists and make this village a tourist attraction, thereby increasing the source of income for the community and the Gunungkidul Regency Government. So, researchers In order to realize this, it is necessary to analyze the village potential and review the existing facilities and infrastructure in Girijati Village. The research data were collected through observation, documentation, and some literature. This community service is expected to provide counseling that can be implemented by Girijati Village in the future.